Pharmaceutical Co-Crystal Formulation of Rivaroxaban with Niacinamide: Preparation, Characterization, and In Vitro Release Evaluation - Solomon, Cristina; Sarbu, Iulian; Anuța, Valentina; Ozon, Emma Adriana; Musuc, Adina Magdalena; Rusu, Adriana; Surdu, Vasile Adrian; Chandak, Abhay; Gavriloaia, Roxana Mariuca; Fița, Ancuța Cătălina; Nită, Denisa Teodora; Mitu, Mirela Adriana (MDPI AG, 2026)
The present study investigates the co-crystallization process of rivaroxaban (RIV), a poorly water-soluble potent oral anticoagulant, with niacinamide (NIA), a highly soluble and pharmaceutically acceptable co-crystal former, in two different molar ratios (1:1 and 1:2). The aim was to enhance the physicochemical and biopharmaceutical properties of rivaroxaban such as dissolution rate and aqueous solubility, by forming stable co-crystals through a solvent evaporation technique. The resulting co-crystals (RIV-NIA, 1:1 co-crystallization compound, F1 and RIV-NIA, 1:2 co-crystallization compound, F3) were characterized using scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), powder X-ray diffraction (XRD) and thermal analysis, which confirmed the formation of a new rivaroxaban–niacinamide co-crystalline phase. In vitro dissolution studies confirmed a significant enhancement in the dissolution rate of the two obtained co-crystals. These findings suggest that stoichiometric variation plays an important role in co-crystal performance and in improving solubility compared with the pure drug. Also, the obtained results suggest that niacinamide is an effective coformer for improving the dissolution and physicochemical properties of rivaroxaban.
Keywords: rivaroxaban; niacinamide; pharmaceutical co-crystals; dissolution enhancement; co-crystallization